A Reference Section Through Fast‐Spread Lower Oceanic Crust, Wadi Gideah, Samail Ophiolite (Sultanate of Oman): Whole Rock Geochemistry. Issue 6 (17th June 2022) - Garbe‐Schönberg, Dieter; Koepke, Jürgen; Müller, Samuel; Mock, Dominik; Müller, Tim
Abstract: Due to its inaccessibility, no complete and coherent data set exists for the composition of modern fast‐spreading oceanic crust. We sampled outcrops through 6, 500 m of fossil oceanic crust in the Oman Ophiolite (Wadi Gideah Transect) that is regarded as best analogue of fast‐spreading crust on land. Here we report a complete set of whole‐rock major and trace element data displaying systematic and contrasting compositional trends in lower and upper gabbros being correlated with stratigraphic depth. A significant discontinuity in crystallization regime is observed at ∼3, 525 m above the mantle‐crust boundary: gabbros below ∼3, 525 m have in general very low incompatible element mass fractions which develop upwards in a barely noticeable way to more differentiated compositions while Mg# decreases. More pronounced trends indicating progressive fractionation of ascending melts can be observed for incompatible elements and their element ratios as a consequence of in situ crystallization. Locally, more variable compositions within narrow depth intervals testify for advanced differentiation in situ within individual sills. Gabbros above ∼3, 525 m become significantly more evolved and show considerable variations in composition. Fractional crystallization and mixing processes in a transient axial melt lens control the composition of isotropic "varitextured" gabbros and sheeted dike basalts where fractionation of high field strength elemental ratios is minor. New average compositions of fast‐spread (paleo) oceanic crust are reported for major and 38 trace elements. Comparison with new data from Wadi Khafifah close to Wadi Gideah suggests robustness of crustal accretion processes in both space and time. Plain Language Summary: Oceanic crust covers more than two‐thirds of Earth's surface but, due to limited accessibility, no single coherent compositional profile that would allow for understanding the processes how oceanic crust is formed has been obtained up to now. We sampled a transect through 6.5 km of fossil lower oceanic crust of the Samail ophiolite (Sultanate of Oman, Wadi Gideah) that is regarded as best analogue of fast‐spreading oceanic crust on land, and analyzed all samples with a wide selection of techniques. Here, we present whole rock data and see systematic compositional trends correlating with stratigraphic depth. Distribution trends of incompatible trace elements suggest that lower, layered gabbros are made of cumulus crystals that crystallize in situ, separating from the ascending parental magma. We also find gabbros with variable compositions at intermediate depth intervals that could originate from melts crystallizing and differentiating in sills. In contrast, compositions of upper non‐layered gabbros above ∼3, 525 m above the mantle‐crust boundary are controlled by fractional crystallization and mixing processes in transient melt lenses. New average compositions of (paleo) oceanic crust are reported for major and 38 trace elements. Comparison with new data from Wadi Khafifah close to Wadi Gideah suggests robustness of accretion processes in both space and time. Key Points: A coherent compositional transect through fossil oceanic crust for major and 38 trace elements, compositions for Samail oceanic crust Systematic but contrasting compositional trends correlate with stratigraphic depth over 6, 500 m of plutonic crust A discontinuity at ～3, 525 m above Moho separates lower cumulate gabbros crystallized in situ from upper gabbros fractionated in melt lens